INFORMATION SYSTEMS CONTROL OF GOODS AND PAYMENT OF PT. VINOLI MAKMUR - MOH. Imron Rosyadi; Don Elsafitra, SKom (Jurnal Sistem Informasi, 2003)
In this era of globalization the world today to simplify and expedite a job, the required information accurately. Computers indispensable role in solving a variety of jobs associated with the storage, preparation of reports and update existing data. PT. Vinoli Makmur Jakarta, is a company engaged in the manufacture of snack foods such as snacks, jelly, chocolate and others.  The Company has marketed its products in nearly all regions and also outside jabotabek jabotabek such as Lampung, Solo, Bandung, and others. Because the amount of circulation of goods and transactions every day so much, the computerization of all transactions is a must.